A first course in stochastic calculus - Arguin, Louis-Pierre, 1979- (Providence, Rhode Island : American Mathematical Society, 2022)
"The pdf contains a draft title page, draft copyright page and a draft manuscript"--
Includes bibliographical references and index.
Keywords: Stochastic analysis; Calculus; Stochastic processes; Probability theory and stochastic processes {For additional applications, see 11Kxx, 62-XX, 90-XX, 91-XX, 92-XX, 93-XX, 94-XX} -- Stochastic processes -- General theory of processes; Probability theory and stochastic processes {For additional applications, see 11Kxx, 62-XX, 90-XX, 91-XX, 92-XX, 93-XX, 94-XX} -- Stochastic analysis [See also 58J65] -- Stochastic integrals; Game theory, economics, social and behavioral sciences -- Mathematical finance -- Derivative securities; Game theory, economics, social and behavioral sciences -- Mathematical finance -- Numerical methods (including Monte Carlo methods).